Immune Activities in Choroids of Visually Impaired Smyth Chickens With Autoimmune Vitiligo - Sorrick, Jordan; Huett, Wilson; Byrne, Kristen A.; Erf, Gisela F. (Frontiers in Medicine, 2022)
Vitiligo is a common dermatological disorder affecting 1-2% of the world’s population. It is characterized by postnatal, autoimmune destructions of melanocytes in the skin, resulting in patches of depigmentation. Autoimmunity in vitiligo may also affect melanocytes in non-integumental tissues, including eyes where choroidal melanocytes are the target of the autoimmune response. The Smyth line (SL) of chicken is the only animal model that spontaneously and predictably develops all clinical and biological manifestations of autoimmune vitiligo. In SL vitiligo (SLV), destruction of epidermal melanocytes in growing feathers (GF) involves a melanocyte-specific, Th1-mediated cellular immune response. Smyth chickens may also exhibit uveitis and vision impairment. Previous studies established a strong association between SLV and vision impairment, including similar pathology in affected eyes and GF. To determine the presence, types, and activities of choroid infiltrating mononuclear cells, we collected eyes before, near onset, and during active SLV from sighted, partially blind, and blind SL chickens. All SL chickens with vision impairment had SLV. Immunohistochemistry and q-RT-PCR analyses revealed mononuclear cell and cytokine expression profiles in the autoimmune destruction of melanocytes in choroids that are identical to those described in GF, demonstrating the systemic nature of autoimmunity against melanocytes in SLV. Additionally, we observed aberrant melanogenesis in SL eyes. The immunopathogenesis in SL vision impairment resembles human vitiligo-associated ocular diseases, especially Vogt-Koyanagi-Harada syndrome and sympathetic ophthalmia. Hence, the Smyth chicken autoimmune vitiligo model provides opportunity to expand our understanding of spontaneous autoimmune pigmentation disorders and to develop effective treatment strategies.